2001
DOI: 10.1093/ajcn/74.5.687
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein, carbohydrate, and fat enhance memory performance in the healthy elderly

Abstract: Background: Dietary carbohydrates can improve memory. Whether these effects are related to elevations in blood glucose or to energy ingestion is unknown. Objectives: Our objectives were to determine 1) the influence of isoenergetic protein-, carbohydrate-, and fat-containing drinks on cognitive performance and 2) whether the time period after ingestion affects cognition. Design: After fasting overnight, 11 men and 11 women aged 61-79 y consumed either a 300-mL drink containing 774 kJ as pure protein (whey), ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 46 publications
3
79
0
2
Order By: Relevance
“…In addition, several studies showed that eating breakfast can improve cognitive performance and attention-concentration compared with omitting breakfast [18][19][20], but the effect of each macronutrient was not defined because of various methodologic issues. In fact, the study [21] about the relationship of macronutrients and memory performance indicated all of the macronutrients improved paragraph recall 15 min after ingestion, suggesting that energy intake can enhance specific aspects of cognition, in addition to the effects of energy ingestion on memory, each macronutrient enhanced performance on various tasks, possibly via unique mechanisms. Indeed, all three kinds of macronutrients led to an initial, robust improvement on delayed paragraph recall.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, several studies showed that eating breakfast can improve cognitive performance and attention-concentration compared with omitting breakfast [18][19][20], but the effect of each macronutrient was not defined because of various methodologic issues. In fact, the study [21] about the relationship of macronutrients and memory performance indicated all of the macronutrients improved paragraph recall 15 min after ingestion, suggesting that energy intake can enhance specific aspects of cognition, in addition to the effects of energy ingestion on memory, each macronutrient enhanced performance on various tasks, possibly via unique mechanisms. Indeed, all three kinds of macronutrients led to an initial, robust improvement on delayed paragraph recall.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, all three kinds of macronutrients led to an initial, robust improvement on delayed paragraph recall. Each macronutrient may exert different effects on cognition by additional, unique mechanisms [21]. Human beings should not ingest pure protein, carbohydrate, or fat, but should pay attention to the content of the various macronutrients reasonably matched.…”
Section: Introductionmentioning
confidence: 99%
“…The 25 g mixture will obviously provide only 25% of the caloric load of the 100 g mixture, so greater feelings of hunger would be expected 5-7 hours after the mixture ingestion, which is when measures are usually obtained. Furthermore, when humans ingest a meal, it enhances memory, 96 which raises the possibility that memory will be enhanced by the 100 g mixture relative to the 25 g mixture 5 hours later. For these reasons, the use of a 25 g control mixture is not recommended, and results obtained using this methodology should be accepted with caution.…”
mentioning
confidence: 99%
“…Girls, but not boys, recalled more words after consuming the milk-containing beverages, suggesting that both sex and macronutrient composition interact to affect memory performance. In healthy older adults (12), despite difference in the glycemic response, both dietary protein and fat improved memory performance similar to carbohydrate. Thus, multiple mechanisms other than an increase in blood glucose contribute to improvements in memory performance.…”
Section: Discussionmentioning
confidence: 90%